2009
DOI: 10.17221/66/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vasoactive intestinal polypeptide, substance P and neuropeptide Y in jejunal enteric nerves is altered in rabbits suffering from long term Trichinella spiralis infection: an immunohistochemical study

Abstract: ABSTRACT:In the early intestinal stage of infection with the nematode Trichinella spiralis alterations in gut motility and chemical code of enteric neurons are observed. The present study was designed to characterize the changes in expression pattern of vasoactive intestinal polypeptide (VIP), substance P (SP) and neuropeptide Y (NPY) in enteric nerves of the rabbit jejunum occurring during long-lasting trichinellosis (35 and 42 days). Sections of the jejunum from healthy and T. spiralis-infected rabbits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Earlier studies have shown that NPY‐positive nerve fibers and neuronal cell bodies are present in the submucosal layer as well as the myenteric plexus . Similarly, we also observed NPY immunoreactive cells in the myenteric plexus surrounding the jejunum and the network of beaded fibers spread over the myenteric plexus through the villi.…”
Section: Discussionsupporting
confidence: 86%
“…Earlier studies have shown that NPY‐positive nerve fibers and neuronal cell bodies are present in the submucosal layer as well as the myenteric plexus . Similarly, we also observed NPY immunoreactive cells in the myenteric plexus surrounding the jejunum and the network of beaded fibers spread over the myenteric plexus through the villi.…”
Section: Discussionsupporting
confidence: 86%
“…Its higher presence with the connection of improved intestinal barrier and antiinflammatory and anti-bacterial properties after the HMB supplementation can help to keep a healthy gut (Xiong et al, 2019). Moreover, other studies on several animals have showed that VIP expression is changed by the inflammatory process, which correlates with altered smooth muscle contractility (Arciszewski et al, 2009).…”
Section: Discussionmentioning
confidence: 99%